Compatibilizing role of carbon nanotubes in poly(vinyl alcohol)/starch blend. Issue 1 (3rd October 2014) - Jose, Jobin; De, S. K; AlMa'adeed, Mariam Al‐Ali; Dakua, Jolly Bhadra; Sreekumar, P. A; Sougrat, Rachid; Al‐Harthi, Mamdouh A.; Tester, Richard F.
Abstract Polymer nanocomposites based on poly(vinyl alcohol)/starch blend and carbon nanotubes (CNT) were prepared by solution mixing, followed by casting. Glycerol was used as a plasticizer and added in the starch dispersion. The uniform dispersion of CNT in water before mixing with PVA/starch blend, was achieved by using an Ultrasonicator probe. The composites were characterized by measurement of tensile properties, thermal analysis, FE‐SEM, TEM, XRD studies, and water uptake. It was observed that the decrease in tensile strength, modulus, and elongation at break on addition of starch into PVA can be arrested by incorporation of CNT. The strong physical bonding such as hydrogen bonding among the hydroxyl groups of polymer components and oxygen containing groups on CNT surface resulted in a more tortuous path for the water to follow, lowering of water uptake. Thermal analysis and spectroscopic images showed an increase in blend homogeneity in the presence of CNT.